Implementation of KPU Coordination with PPK and PPS in the General Election in Padang Pariaman District - Rika Mardesya Vitri; Fachri Adnana (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Abstract This study aims to identify and analyze the factors influencing coordination between the General Election Commission (KPU), the Sub-district Election Committees (PPK), and the Village Election Committees (PPS) in the implementation of elections in Padang Pariaman Regency. The research employs a qualitative method with a case study approach, involving in-depth interviews with members of the KPU, PPK, and PPS to obtain primary data on issues affecting coordination. The results reveal several obstacles in coordination, including inadequate supervision and periodic evaluation, a lack of intensive guidance and assistance during the election process, and limited human resources at the regional level, which hinder effective evaluations. Additionally, the lack of structured communication and coordination among the involved parties exacerbates the inefficiency of coordination. This study provides several recommendations, such as improving routine supervision and evaluations, increasing the number of supervisory personnel, and simplifying evaluation and reporting systems. By addressing these issues, it is expected that election implementation can proceed more effectively and smoothly, minimizing obstacles that may delay decision-making processes and coordination in the field. Keywords: Implementation of Coordination, KPU, PPK and PPS, The 2024 Election